Modelling the impact of cyclic hypoxia on cell-cycle regulation in cancer cells - Celora, G (2022)
In vivo observations show that oxygen levels in tumours can fluctuate on fast timescales. As a result, cancer cells can be periodically exposed to pathologically low oxygen levels; a phenomenon known as cyclic hypoxia. Even though in vitro models of cyclic hypoxia exist, they fail to capture the complex and heterogeneous oxygenation dynamics of real tumours. Mathematical models can help to overcome current experimental limitations and, by doing so, offer new insights into the biology of cyclic hypoxia by predicting cell responses to a wide range of cyclic dynamics. Recent experimental evidence suggests that cyclic hypoxia alters the progression of cancer cells along the cell-cycle. In this thesis, we use a range of mathematical approaches to study cell-cycle dysregulation in cyclic hypoxia and its impact on the growth and survival of cell cultures.